Perceived menstrual cycle-related symptoms throughout four cycles in elite South American futsal athletes - Larson, A.; Gamboa, C. (International Journal of Exercise Science Conference Proceedings, 2025)
Previous research suggests menstrual cycle (MC) phases have minimal impact on exercise performance; however, less is known about the influences of MC phases on day-to-day training variables, particularly those that are subjective in nature. Mobile apps designed to track MCs are becoming increasingly popular for exercise planning but the utility of these tools for capturing MC-related changes in training/performance variables has not been fully explored. PURPOSE: This study aimed to identify how the four phases of the MC (menstrual, follicular, ovulatory, and luteal), predicted by the Fitr Woman App, influence the frequency of daily, self-reported perceptions of decreased motivation (DM), heavy legs (HL), fatigue (F), and muscle aches (MA), over four consecutive MCs in female futsal players. METHODS: Six elite South American futsal players (age 21 ± 4.0 years) tracked their MCs and daily perceptions of DM, HL, F, and MA for four months using the Fitr Woman app. To account for phase-length differences, the % of days that each symptom was reported was calculated relative to the total number of days in each respective MC phase. A repeated-measures ANOVA was used to compare group-mean symptom frequencies across MC phases over four cycles and identify if there were cycle-to-cycle differences in mean % of days with reported DM, HL, F, and MA, respectively, for each MC phase. Significance was accepted at p<0.05. RESULTS: No statistically significant differences were found in the frequency of DM, F, and HL symptoms across the MC phases; however, frequency of MA was lower during the follicular phase (19% ± 13%; p = 0.02) and the ovulatory phase (15% ± 12%; p = 0.01) compared to the menstrual phase (27% ± 10%), with large effect sizes (partial n² = 0.46 and 0.52, respectively). There were significant month-to-month differences in reported mean frequency of % of days with reported DM, HL, F, and MA respective to each MC phase suggesting no clear phase-related, month-to-month pattern (p<0.05 for all). CONCLUSION: This study supports previous research indicating MC phase doesn`t necessarily predict the presence of DM, HL, F, or MA and MC-tracking apps may not be useful for predicting changes in these variables. It is likely that other training-related variables and lifestyle factors have a more profound effect on perceptions of DM, HL, F, or MA.